Advances in Understanding Micro‐ and Nanoplastic Toxicity on Farmed Fish and Emerging Nutritional Interventions - Quansen Xie; Fang Chen; Xiaoping Huang; Jun Wang; Dizhi Xie (Reviews in Aquaculture, 2026)
Micro‐ and nanoplastics (MNPs), encompassing microplastics (MPs, diameters

Environmental Pollutant‐Induced Disruption of Lipid Droplet Homeostasis in Aquatic Animals: Molecular Mechanisms and Cross‐Scale Health Effects - Xiaoping Huang; Dizhi Xie; Jun Wang (Reviews in Aquaculture, 2025)
The disruption of lipid metabolic homeostasis in aquatic animals under pollutant stress has become a pivotal research frontier in environmental toxicology. As a crucial adaptive strategy, aquatic animals employ lipid droplet (LD)‐mediated metabolic reprogramming to facilitate energy reallocation and oxidative stress defense in response to environmental pressures. This review analyzes the regulatory mechanisms of LDs, focusing on molecular pathways for their biogenesis, storage, and catabolism. We also explore how pollutants like heavy metals, micro/nanoplastics (MNPs), and fungicides cause LD abnormalities by interfering with multiple targets. Key mechanisms include disrupted lipid metabolism, altered redox signaling, impaired organelle communication, and endocrine interference. By integrating multiscale evidence from cellular dysfunction to population adaptability decline, we establish a novel “pollutant‐LD homeostasis‐health effect” framework that delineates the spatiotemporal cascade effects of LD homeostasis disruption. This study identifies LD‐associated biomarkers as sensitive indicators for monitoring aquatic pollution. These findings establish critical connections between subcellular metabolic responses and ecosystem‐level health outcomes.